Made In Hong Kong - Lorenzo, Isa (Likhaan: The Journal of Contemporary Philippine Literature; Vol 18 No 1 (2024): LIKHAAN 18 The Journal of Contemporary Philippine Literature, 2024)
In “Made in Hong Kong,” Sara, a young Pinay, goes to Hong Kong to work as a maid. She makes friends with a group of four other maids called the Palanggas, but Cherry’s employer tries to rape her, while Julie, the fiercest of them all, is burned. In the end, Sara decides to find a new employer, hopefully one who is more humane.